Mothers' Experiences in Caring for Children Diagnosed with Covid-19: A Phenomenological Study - Dessie Wanda; Yayah Yayah; Happy Hayati; Nani Nurhaeni (Department of Nursing Universitas Jenderal Soedirman, 2024)
Mothers, as the primary caregivers are most likely affected when children are exposed to the COVID-19 pandemic. A few studies in Eastern countries, particularly in Indonesia, explored how mothers were affected by their children's hospitalization due to COVID-19. Indonesia and most eastern countries applied collectivism, which is essential for togetherness. This study aimed to identify mothers' experiences caring for children diagnosed with COVID-19. A phenomenological approach was used, and the data were collected through in-depth interviews with 15 mothers recruited using a purposive sampling technique. Thematic analysis was performed to analyze the data by compiling mothers' experiences caring for children diagnosed with COVID-19 at home and in hospitals. Five themes were revealed: (1) feeling guilty when the child was confirmed positive for COVID-19, (2) feeling worried about the health of the child but thinking positively and becoming stronger, (3) feeling grateful to be able to do the isolation together with the child, (4) making an effort to help the child become cured of COVID-19 and (5) feeling relieved when their children had relatively mild symptoms during isolation. Mothers faced psychological problems including feeling guilty about their child's condition, but then happy when they were hospitalized and recovering together.